Using the Internet to Help With Diet, Weight, and Physical Activity: Results From the Health Information National Trends Survey (HINTS) - McCully, Scout N; Don, Brian P; Updegraff, John A (JMIR Publications, 2013)
BackgroundThe Internet offers a viable platform for cost-effective and wide-reaching health interventions. However, little is known about use of the Internet to help with diet, weight, and physical activity (DWPA) using a nationally representative sample from the United States. ObjectiveTo (1) assess the demographic characteristics of people who use the Internet to help with DWPA, (2) assess whether usage trends changed over time, and (3) investigate the associations between using the Internet for DWPA and health behaviors. MethodsData on Internet users from the 2007 and 2011 iterations of the Health Information National Trends Survey (HINTS), N=4827 were analyzed using multiple logistic regression to determine the demographic correlates of using the Internet for help with DWPA. Multiple linear regression was used to test the associations between Internet use for DWPA and three health behaviors: fruit intake, vegetable intake, and physical activity. ResultsA larger percentage of Internet users used the Internet for DWPA in 2011 (42.83%) than in 2007 (40.43%). In general, Internet users who were younger (OR 0.98, P<.001), more educated (OR 1.40, P<.001), married (OR 1.06, P=.03), of a minority race (non-Hispanic blacks: OR 1.14, P=.02; Hispanics: OR 1.42, P=.01), and who had a higher Body Mass Index (BMI) (OR 1.04, P<.001) were more likely to use the Internet for DWPA. Across survey years, gender was not associated with using the Internet for DWPA (OR 1.03, P=.12), but there was a significant interaction between survey year and gender (OR 1.95, P=.002); in 2007, men were more likely to use the Internet for DWPA, but women were more likely to do so in 2011. Using the Internet for DWPA was associated with more vegetable intake (B=.22, P=.002), more fruit intake (B=.19, P=.001), and more moderate exercise (B=.25, P=.001), although the strength of the associations between using the Internet for DWPA and fruit intake and exercise was weaker in 2011 than in 2007. ConclusionsContrary to prior research, our population-level study did not show a pronounced gender difference in the use of the Internet for DWPA. Our results support the increasing viability of the Internet as a platform for behavior change intervention, as a growing percentage of Internet users are turning to the Internet for help with DWPA. Additionally, using the Internet for DWPA is associated with better DWPA-related health behaviors.